2022
DOI: 10.3389/fmed.2022.826746
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics Approaches for Genetic Characterization of SARS-CoV-2 Lineages

Abstract: The genome of the Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2), the pathogen that causes coronavirus disease 2019 (COVID-19), has been sequenced at an unprecedented scale leading to a tremendous amount of viral genome sequencing data. To assist in tracing infection pathways and design preventive strategies, a deep understanding of the viral genetic diversity landscape is needed. We present here a set of genomic surveillance tools from population genetics which can be used to better understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Using a Bayesian statistical model that estimates relative growth rates per lineage, this study tracked the fraction of genomes from different lineages in each local authority, accounting for differences in local epidemiological dynamics including in the rate of introduction of different lineages. Using classic population genetics statistical tools, Mostefai et al [91] detected extensive population structure in viral genetic data from the first year of the pandemic, and characterized lineage expansion worldwide using changes in Tajima's D statistics [92] over time. Using birth-death processes, Scholer et al [93] were able to quantify the impact of interventions on the extinction probability of deleterious SARS-CoV-2 variants, which is applicable in the initial outbreak of a new variant of concern.…”
Section: Population Genetics Of Viral Evolutionmentioning
confidence: 99%
“…Using a Bayesian statistical model that estimates relative growth rates per lineage, this study tracked the fraction of genomes from different lineages in each local authority, accounting for differences in local epidemiological dynamics including in the rate of introduction of different lineages. Using classic population genetics statistical tools, Mostefai et al [91] detected extensive population structure in viral genetic data from the first year of the pandemic, and characterized lineage expansion worldwide using changes in Tajima's D statistics [92] over time. Using birth-death processes, Scholer et al [93] were able to quantify the impact of interventions on the extinction probability of deleterious SARS-CoV-2 variants, which is applicable in the initial outbreak of a new variant of concern.…”
Section: Population Genetics Of Viral Evolutionmentioning
confidence: 99%
“…In computational biology, dimensionality reduction techniques are commonly used to simplify the representation and analysis of complex datasets, like viral sequencing data, and to uncover inherent data biases. These techniques, which have seen significant improvements with the rise of high-dimensional data, include Principal Component Analysis (PCA) (Novembre et al 2008; Mostefai et al 2022), often used for summarizing human genetic data, t-SNE (Platzer 2013; Tamazian et al 2022) for analyzing local structures, and PHATE (Moon et al 2019), a novel method that allows visualization of both global and local structures in highdimensional data. Despite the potential of these methods, their application to the extensive SARS-CoV-2 data has been limited, often confined to analyzing consensus sequences (Hozumi et al 2021; B.…”
Section: Introductionmentioning
confidence: 99%
“…Population genetic approaches have been used to monitor the frequency of mutations, alternative alleles, lineage spread and population structure, and evolutionary dynamics of SARS-CoV-2 [14, 15]. These approaches have allowed for the detection of recurrent mutations and facilitated the visualization of genomic variation and lineage spread [14]. Previous population genetic studies of polymorphisms have revealed that SARS-CoV-2 genomes exhibit regional population structure in SARS-CoV-2 populations [13].…”
Section: Introductionmentioning
confidence: 99%